Contributions to the modeling and simulation of an automatic package classification system to improve decision-making in line balancing - Acosta, Esteban (2025)
The growth of e-commerce has led to an increase in the complexity of automatic sorting systems (Sorters), especially evident during the COVID-19 pandemic. This is reflected in the growing number of destinations, variety of products, reduced batch sizes, diversity in box dimensions, varying routes, and the need for rapid response times, among other factors. These complexities hinder decision-making in the s ystem, particularly in developing a line balancing program for package unloading lines from the Sorter. Therefore, tools that support improved decision-making are required. This publication contributes, on one hand, to the conceptual modeling of the system using the IDEF-SIM conceptual modeling technique to better understand it. On the other hand, it contributes to the construction of the simulation model using the FlexSim® software. Finally, a heuristic-based simulation optimization methodology is proposed to enhance decision-making in balancing the sorting line.